Analysis Of Traders' Preparedness Behavior In Preventing Fires At The Masomba Market, Palu City - Muhammad Sabri Syahrir; Herbourina Bonita, A. Ferina; Ummu Kamilah Kodrat (Sean Institute, 2024)
Based on data from the Palu City Fire Department, fire incidents in Palu City tend to increase from 2018 to 2022. Masomba market is one of the traditional markets in Palu City which frequently experiences fires. Based on initial observations made, a major fire hit the Masomba market in Palu City on Wednesday evening, November 30 2022. The aim of this research is to analyze the preparedness behavior of market traders in dealing with fires at the Masomba Market in Palu City. This research uses quantitative methods with a cross sectional approach. The population in this study was 274 traders in the Masomba market in Palu City. The sampling technique in this research was determined by simple random sampling with a total sample of 73 respondents. Data collection uses a questionnaire. The data tests used in this research are univariate and bivariate tests (Chi-Square Test). The results of the research show that there is no relationship between knowledge and attitudes towards traders' preparedness in dealing with fires at the Masomba market, but in terms of training there is a relationship between training and traders' preparedness in fighting fires at the Masomba market. The suggestions in this research are that Masomba market traders are expected to take part in training held by the Palu City Industry and Trade Service or the Palu City Fire and Rescue Service.